Technology Entrepreneurship Project (ENT 600) : Samsung Electronics Malaysia Sdn. Bhd / Nur Damia Auni Ismail - Ismail, Nur Damia Auni (2021)
Samsung Malaysia Electronics SME is one of the leaders in consumer electronics industry in an international scale. The business is divided into three large segments of consumer electronics, IT & mobile communications and device solutions. One of the products that have been produced by Samsung is a vacuum. This vacuum is one of a home appliance which is categories as device solution. Samsung produce a several types of vacuum with a different uses and design. The latest design is Powerbot Vacuum Machine. The objectives of this study are to analyze the problem that Samsung had faced and provide some solution to overcome the problem by give some recommendation to improve the product. After doing company analysis, there are several problems that have been found about Powerbot Vacuum Machine. The problems are the suction is weak, fails to return to charging station and always shows an error code. However, they also received complaints from the customer because of the cleaning work became low after a few month of using when had this problem. From this problem, there are some recommendation and solution to overcome this problem. Samsung need to innovate more about this product to fullfill the customer need as soon as possible when detecting a problem after using it.